Don't keep silent [large type] - Goddard, Elizabeth (Goddard, Elizabeth. Uncommon justice, 2021)
"Investigative reporter Reagan Burke will go anywhere and do anything to find her missing sister-in-law, even if it means facing Liam McKade, a man who almost lost his life saving hers. Their search grows darker and more treacherous, bringing them full circle when the past danger they both tried to flee catches up to them"--